Do Infants Represent the Face in a Viewpoint-Invariant Manner? Neural Adaptation Study as Measured by Near-Infrared Spectroscopy - Kobayashi, Megumi; Otsuka, Yumiko; Nakato, Emi; Kanazawa, So; Yamaguchi, Masami K.; Kakigi, Ryusuke (Frontiers in Human Neuroscience, 2011)
Recent adult functional magnetic resonance imaging (fMRI) studies reported that face-sensitive cortical areas showed attenuated responses to the repeated presentation of an identical facial image compared to the presentation of different facial images (fMRI-adaptation effects: e.g., Andrews and Ewbank, 2004). Building upon this finding, the current study, employing the adaptation paradigm, used near-infrared spectroscopy (NIRS) to explore the neural basis of face processing in infants. In Experiment 1, we compared hemodynamic responses in the bilateral temporal regions during the repeated presentation of the same face (the same-face condition) and the sequential presentation of different faces (the different-face condition). We found that (1) hemodynamic responses in the channels around the T5 and T6 regions increased during the presentation of different faces compared to those during the presentation of different objects; and that (2) these channels showed significantly lower response in the same-face condition than in the different-face condition, demonstrating the neural adaptation effect in 5- to 8-month-olds as measured by NIRS. In Experiment 2, when faces in both the same-face and different-face conditions were changed in viewpoint, lower hemodynamic responses in the same-face condition were found in 7- to 8-month-olds but not in 5- to 6-month-olds. Our results suggest that faces are represented in a viewpoint-invariant manner in 7- and 8-month-old infants.